IMPLEMENTASI METODE EXPERIENTAL LEARNING DI SMP CAHAYA QUR’AN LAMONGAN - Azizah, Nur; Nur Azizah; Wardatul Karomah; Khubni Maghfirotun (INSTITUT AGAMA ISLAM TARBIYATUT THOLABAH LAMONGAN, INDONESIA, 2025)
This study aims to analyze experiential learning as an innovative strategy to enhance holistic competence. Holistic competence is closely related to intellectual, spiritual, emotional, and physical intelligence. It encompasses excellence and achievement in the cognitive (head), psychomotor (hand), and affective (heart) domains, aligning with the goals of education to integrate affective, mental, and psychomotor outcomes. This approach combines comprehensive understanding with hands-on activities. The practical application of this method requires well-planned stages of design, implementation, and evaluation to achieve the desired learning objectives. This research employs a qualitative case study approach to explore experiential learning as an innovative strategy for enhancing holistic competence, utilizing interviews, documentation, and observation as data collection methods. The findings show that experiential learning effectively supports the development of holistic competence in line with educational objectives. For instance, in the Islamic jurisprudence (fiqh) subject matter related to animal slaughtering (niyyah), students engage in group-based projects involving the slaughter, cleaning, and cooking of chickens. In the topic of corpse care (jenazah), students use training mannequins for hands-on practice. Information and Communication Technology (ICT) materials focus on practical skills with tangible outputs. Other implementations include producing short films based on the Lubabul Hadith text, writing books each semester, and developing soft skills such as public speaking.